Phenotype-genotype correlations in Leigh syndrome: new insights from a multicentre study of 96 patients. Issue 1 (3rd November 2017) - Sofou, Kalliopi; de Coo, Irenaeus F M; Ostergaard, Elsebet; Isohanni, Pirjo; Naess, Karin; De Meirleir, Linda; Tzoulis, Charalampos; Uusimaa, Johanna; Lönnqvist, Tuula; Bindoff, Laurence Albert; Tulinius, Már; Darin, Niklas
Abstract : Background: Leigh syndrome is a phenotypically and genetically heterogeneous mitochondrial disorder. While some genetic defects are associated with well-described phenotypes, phenotype-genotype correlations in Leigh syndrome are not fully explored. Objective: We aimed to identify phenotype-genotype correlations in Leigh syndrome in a large cohort of systematically evaluated patients. Methods: We studied 96 patients with genetically confirmed Leigh syndrome diagnosed and followed in eight European centres specialising in mitochondrial diseases. Results: We found that ataxia, ophthalmoplegia and cardiomyopathy were more prevalent among patients with mitochondrial DNA defects. Patients with mutations in MT-ND and NDUF genes with complex I deficiency shared common phenotypic features, such as early development of central nervous system disease, followed by high occurrence of cardiac and ocular manifestations. The cerebral cortex was affected in patients with NDUF mutations significantly more often than the rest of the cohort. Patients with the m.8993T>G mutation in MT-ATP6 gene had more severe clinical and radiological manifestations and poorer disease outcome compared with patients with the m.8993T>C mutation. Conclusion: Our study provides new insights into phenotype-genotype correlations in Leigh syndrome and particularly in patients with complex I deficiency and with defects in the mitochondrial ATP synthase.